Small intestine remodeling in male Goto–Kakizaki rats - Joice Naiara Bertaglia Pereira; Gilson Masahiro Murata; Fabio Takeo Sato; Aline Rosa Marosti; Carla Roberta de Oliveira Carvalho; Rui Curi (Physiological Reports, 2021)
Abstract Background Obesity is associated with the development of insulin resistance (IR) and type‐2 diabetes mellitus (T2DM); however, not all patients with T2DM are obese. The Goto–Kakizaki (GK) rat is an experimental model of spontaneous and non‐obese T2DM. There is evidence that the intestine contributes to IR development in GK animals. This information prompted us to investigate small intestine remodeling in this animal model. Methods Four‐month‐old male Wistar (control) and GK rats were utilized for the present study. After removing the small intestine, the duodenum, proximal jejunum, and distal ileum were separated. We then measured villi and muscular and mucosa layer histomorphometry, goblet cells abundance, total myenteric and submucosal neuron populations, and inflammatory marker expression in the small intestinal segments and intestinal transit of both groups of animals. Key Results We found that the GK rats exhibited decreased intestinal area (p < 0.0001), decreased crypt depth in the duodenum (p = 0.01) and ileum (p < 0.0001), increased crypt depth in the jejunum (p < 0.0001), longer villi in the jejunum and ileum (p < 0.0001), thicker villi in the duodenum (p < 0.01) and ileum (p < 0.0001), thicker muscular layers in the duodenum, jejunum, and ileum (p < 0.0001), increased IL‐1β concentrations in the duodenum and jejunum (p < 0.05), and increased concentrations of NF‐κB p65 in the duodenum (p < 0.01), jejunum and ileum (p < 0.05). We observed high IL‐1β reactivity in the muscle layer, myenteric neurons, and glial cells of the experimental group. GK rats also exhibited a significant reduction in submucosal neuron density in the jejunum and ileum, ganglionic hypertrophy in all intestinal segments studied (p < 0.0001), and a slower intestinal transit (about 25%) compared to controls. Conclusions The development of IR and T2DM in GK rats is associated with small intestine remodeling that includes marked alterations in small intestine morphology, local inflammation, and reduced intestinal transit.